(untitled) (Hilo Analítico, 2021)
Bogotá is the largest receiving territory for the population victim of the armed conflict in the country, housing people who arrive seeking refuge from the situation they have experienced or a temporary or permanent alternative that allows them to resume their lives normally. Out of the entire capital district, Bosa is the second receiving town for victims of the armed conflict due to its particular geographic and population conditions. With an estimated population of 11,000 victims, the town has deployed a series of responses to address the multiple needs presented by these individuals, communities, and groups. This document proposes how the Pablo VI Bosa ESE Hospital, according to the directions of the District Health Secretariat and in the hands of different sectors and local institutions such as the high counseling for victims through the Dignify centers, has developed a response that aims to provide comprehensive health care to the population that addresses not only aspects of psychological and social support but also satisfies fundamental needs within the framework of the guarantee of the right and opens the door for new scenarios for the construction of society such as those that proposes the arrival of the post-conflict